Resident performance in basic perioperative transesophageal echocardiography: Comparing 3 teaching methods in a randomized controlled trial. Issue 36 (September 2019) - Weber, Ulrike; Zapletal, Bernhard; Base, Eva; Hambrusch, Michael; Ristl, Robin; Mora, Bruno
Abstract: Background: Training in transesophageal echocardiography (TEE) is based on hands-on training in the operating room, which is time consuming and therefore limits its experience among anesthesiologists. Medical simulations have been successfully used for training of invasive procedures in many areas. This paper compares the difference in effectiveness of teaching the 11 basic TEE views using either e-learning, simulation based training or hands-on training in the operating room in 3 groups of residents. Methods: We included 51 anesthesia and intensive care residents of all training levels but no prior training in echocardiography in this prospective randomized single-center study. Residents received a tutorial about theoretical knowledge followed by 2 practical study sessions either by e-learning using an online simulator (www.pie.med.utoronto.ca/TEE ), with the simulation mannequin (CAE Vimedix Simulator) or in the operating room. Both, a theoretical multiple choice test (0–50 points) and a practical exam test (0–110 points) on the simulation mannequin had to be completed. The primary endpoint was the post-training scores in the practical and theoretical exams after all training sessions. Results: Residents received significantly higher test scores in both practical and theoretical examinations after training with the simulation mannequin (108.41 ± 2.09, 40.6 ± 5.23, n = 17) compared with e-learning (106.88 ± 4.53, 36 ± 4.76, n = 17) or hands-on training (106.82 ± 2.01, 34.94 ± 4.72, n = 17). Conclusions: Simulation based TEE training provides more effective training than other teaching methods. It is therefore especially suitable for the initial stages of TEE training to acquire psychomotor skills and knowledge of echo-anatomy.